Pb-Zn Deposits and Associated Critical Metals - Zhou, Jia-Xi; Zhang, Changqing; Ren, Tao; Wu, Yue (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
As base metals, zinc and lead are widely developed in various types of deposits. Zinc and lead also form various types of independent deposits and are associated with a variety of critical metals. Zn-Pb deposits occupy an important position in the world, including volcanic-hosted massive sulphide (VHMS/VMS), magmatic-hydrothermal-associated skarn and/or epithermal types, sediment-hosted types (e.g., clastic-hosted sedimentary exhalative, SEDEX; carbonate-hosted Mississippi Valley type, MVT; sandstone-hosted type, SST; and shale-hosted type), and hydrothermal vein types. This Special Issue reprint aims to provide a comprehensive understanding of Zn-Pb deposits and associated critical metals, and promote global prospecting.